Bricktop's Paris : African American women in Paris between the two World Wars - Sharpley-Whiting, T. Denean (SUNY Press, State University of New York Press, 2015)
Tells the fascinating story of African American women who traveled to France to seek freedom of expression. During the Jazz Age, France became a place where an African American woman could realize personal freedom and creativity, in narrative or in performance, in clay or on canvas, in life and in love. These women were participants in the life of the American expatriate colony, which included F. Scott Fitzgerald, Gertrude Stein, and Cole Porter, and they commingled with bohemian avant-garde writers and artists like Picasso, Breton, Colette, and Matisse. Bricktop's Paris introduces the reader to twenty-five of these women and the city they encountered. Following this nonfiction account, T. Denean Sharpley-Whiting provides a fictionalized autobiography of Ada "Bricktop" Smith, which brings the players from the world of nonfiction into a Paris whose elegance masks a thriving underworld.--Publisher website